1977
DOI: 10.1007/bf02533377
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of molecular species of intact serine and ethanolamine phosphatides by argentation chromatography of their trifluoroacetamides

Abstract: An effective resolution of intact phosphatidylserines on the basis of unsaturation has been achieved by conventional argentation thin layer chromatography (TLC) following trifluoracetylaction. The trifluoroacetamides are prepared by treatment with trifluoroacetic anhydride or N-methyl-bis-trifluoroacetamide. The acetamides are resolved with chloroform-methanol-water (65:25:4, v/v/v) on Silica Gel G containing 20% silver nitrate. Subfractions with 0-6 double bonds per molecule were obtained for the phosphatidyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 34 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…CoA and arachidonoyl-CoA (Holub, 1980). As 30% and 50% of the microsomal and total liver phosphatidylserines respectively are saturatedhexaenoic species, and as they also contain 15 times more stearic acid than palmitic acid (Yeung et al, 1977;Bjerve, 1982), this indicates that the Lands & Merkl (1963) pathway does not play any quantitatively significant role in the biosynthesis of rat liver phosphatidylserines. Other, energy-requiring, pathways of phosphatidylserine synthesis have been suggested to explain some observed phenomena in systems investigated in vitro (Hiibscher et al, 1959;Bygrave & Bucher, 1968;Baranska, 1980).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…CoA and arachidonoyl-CoA (Holub, 1980). As 30% and 50% of the microsomal and total liver phosphatidylserines respectively are saturatedhexaenoic species, and as they also contain 15 times more stearic acid than palmitic acid (Yeung et al, 1977;Bjerve, 1982), this indicates that the Lands & Merkl (1963) pathway does not play any quantitatively significant role in the biosynthesis of rat liver phosphatidylserines. Other, energy-requiring, pathways of phosphatidylserine synthesis have been suggested to explain some observed phenomena in systems investigated in vitro (Hiibscher et al, 1959;Bygrave & Bucher, 1968;Baranska, 1980).…”
Section: Methodsmentioning
confidence: 97%
“…Approx. 45% of the phosphatidylserines in the rat liver cell are stearoyl-docosahexaenoyl species, and 30% are stearoyl-arachidonoyl species (Yeung et al, 1977;Bjerve, 1982). It has been suggested that the arachidonoyl species are synthesized mainly by re-acylation of l-acyl-sn-3-glycerophos-* Present address.…”
mentioning
confidence: 99%